Magnetic Decreases (MDs) and mirror modes: two different plasma β changing mechanisms - Tsurutani, B.T.; Lakhina, G.S.; Verkhoglyadova, O.P.; Echer, E.; Guarnieri, F.L. (My University, 2010)
We discuss two different physical processes that create localized high β plasma regions. One is nonlinear wave-steepening, generating magnetic decreases (MDs) by a ponderomotive force. The other is the mirror instability generating alternating high and low β plasma regions. It is demonstrated that MDs and mirror modes are observationally quite different structures. MDs spatially occur in interplanetary space and mirror modes primarily in planetary magnetosheaths. MDs are characterized by: 1) variable (exponentially decreasing number with increasing) angular changes, 2) variable (exponentially decreasing) thicknesses, and 3) no characteristic inter-event spacings. In sharp contrast, mirror modes are characterized by: 1) little or no angular changes across the structures, 2) a characteristic scale size, and 3) are quasiperiodic in nature. Arguments are presented for the recently observed magnetic dips in the heliosheath being mirror mode structures. The sources of free energy for instability are discussed. Both structures are important for energetic particle transport in astrophysical and heliospheric plasmas.
Keywords: Magnetic decreases; Mirror modes; Heliospheric plasmas; Magnetic holes